TELEMEDICINE: THE REVOLUTIONARY ROLE OF INFORMATION TECHNOLOGIES IN MODERN HEALTHCARE SYSTEMS (Modern American Journal of Medical and Health Sciences, 2025)
Telemedicine is one of the fastest-growing fields in modern medicine and is considered one of the most significant achievements of information technology in healthcare. This topic is highly suitable for a research article for several reasons. Numerous scientific articles, analytical reports, practical experiences, and statistical data are available on telemedicine from reputable sources. Countries like India, Saudi Arabia, and the United States have successfully implemented telemedicine, providing concrete examples to support your writing. Initial steps in telemedicine have also been taken in Uzbekistan and other Central Asian countries, allowing the topic to be explored in a national context.